Professional and personal development for teachers: The application of learning following a counselling module - (:unkn) unknown (BRITISH PSYCHOLOGICAL SOC, 1996)
A group of 82 teachers from a wide range of educational settings attended a one-term, 30-hour counselling module which was embedded in a Master's Degree programme in Human Relations. This article reports an evaluation of the extent to which the participants applied this learning in their professional and personal lives. The use of a self-report inventory demonstrated no significant changes in the use of the counselling strategies immediately after the training, but significant changes one year later. This implies a substantial sleeper effect, where the positive effects of the training were appearing well after the module had ended. The study provides information on the general effectiveness of counselling training and in relation to specific counselling strategies. Differences according to age, gender, length of work experience and previous experience of counselling courses were identified. Qualitative reports including interviews, diary reports and goal setting, indicate substantial applications of counselling strategies in both professional and personal life.